Hydrogen Bond Induced Green Solvent Processed High Performance Ternary Organic Solar Cells with Good Tolerance on Film Thickness and Blend Ratios. (27th May 2019) - Du, Xiaoyang; Lu, Xi; Zhao, Juewen; Zhang, Yuqing; Li, Xinrui; Lin, Hui; Zheng, Caijun; Tao, Silu
Abstract: For comprehensive development of organic solar cells (OSCs), some factors such as environmental stability, low cost, insensitive film thickness, component contents tolerance, and green preparation processes are equally crucial to achieve high power conversion efficiencies (PCEs). In this work, a small molecule 3‐(diethylamino)‐7‐imino‐7H‐benzo[4, 5]imidazo[1, 2‐a]chromeno[3, 2‐c]pyridine‐6‐carbonitrile (DIBC), which is commercially available at low cost, is utilized to realize high‐performance ternary OSCs. Demonstrated via Fourier transform infrared and 2D‐ 1 HNMR, DIBC can form hydrogen bond interactions with [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PC71 BM) in solid films. Further electrostatic potential (ESP) calculations indicate that the hydrogen bond interaction enhances the ESP of PC71 BM and accelerates charge transport between donor and acceptor. As a result, poly(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b;4, 5‐b0]dithiophene‐2, 6‐diylalt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐b]thiophene‐)‐2‐carboxylate‐2‐6‐diyl (PTB7‐Th):DIBC:PC71 BM‐based ternary OSC achieves a maximum efficiency of 12.17%, which is the best result of green solvent processed fullerene OSCs at present. It is noteworthy that the ternary OSCs also show great tolerance to film thickness and blend ratios. These unique properties are attributed to the hydrogen‐bond‐linked DIBC and PC71 BM, which modulates molecule distribution and improves film morphology with an interpenetrating network structure. Furthermore, the DIBC containing device also exhibits good thermal and light radiation stability. These results illustrate that intermolecular hydrogen bond interaction has great potential for realizing high‐performance OSCs. Abstract : Intermolecular hydrogen bonding is a potential strategy for organic solar cells to realize low cost, high efficiency, good device and morphology stability, excellent composition, and film thickness tolerance.